130 Juvenile systemic lupus erythematosus related pancreatitis: An uncommon manifestation of a common disease. (April 2019) - Anjani, Gummadi; Singh, Ankita; Pilania, Rakesh; Johnson, Nameirakpam; Vignesh, Pandiarajan; Suri, Deepti; Gupta, Anju; Jindal, Ankur; Singh, Surjit
Abstract : Background: Pancreatitis is a rare but potentially life-threatening complication of systemic lupus erythematosus(SLE).SLE-related pancreatitis can be a presenting manifestation of SLE or may occur during follow-up. Methods: We have reviewed the clinical records of 140 children with SLE between period of 1993–2018.We report 3 children with SLE who presented with acute pancreatitis. Results: Case1–12-year-girl presented with fever and alopecia.Examination revealed pedal oedema, periorbital puffiness, large joint arthritis.Investigations showed anemia, thrombocytopenia, elevated erythrocyte sedimentation rate(ESR), normal renal functions, microscopic hematuria, nephrotic range proteinuria, hypocomplementemia, antinuclear antibody (ANA) 4+, elevated anti double stranded DNA (anti-ds DNA), negative antiphospholipid antibodies (APLA) titre(table).Renal biopsy revealed Class 3 lupus nephritis and initiated on intravenous methylprednisolone.Two days later, she developed severe epigastric pain and vomiting.The pain increased in severity and physical examination revealed marked tenderness in the epigastrium.Serum amylase and lipase were elevated.Clinical possibilities included steroid induced pancreatitis and lupus pancreatitis.In view of severity of symptoms, intravenous methylprednisolone was continued following which she showed a dramatic improvement and normalisation of pancreatic enzymes.There has been no recurrence of pancreatitis over 3 years of follow-up period and remained well on low dose oral prednisolone(5 mg), mycophenolate-mofetil and hydroxychloroquine. Case2-A-6-year-old presented with pain abdomen and vomiting.Physical examination showed epigastric tenderness.Investigations showed anemia, thrombocytopenia, elevated amylase levels(table).Computerised tomography(CT) abdomen revealed acute necrotising pancreatitis.A follow-up ultrasound abdomen revealed a pancreatic pseudocyst.He had a second episode of acute pancreatitis along with anasarca after 3 months which improved with conservative management.Investigation showed anemia, nephrotic range proteinuria and microscopic haematuria(table).ANA was positive with normal complement levels and negative anti-dsDNA titres(table).Lupus band test on skin biopsy was positive.Renal biopsy showed mesangioproliferative-glomerulonephritis with full house pattern.Following the initiation of steroids, he improved and there has been no recurrence of pancreatitis over the next 4 years. Case 3–9 year-girl presented with generalised rash, alopecia for 5 months.She also had pain abdomen for last 2 months.Investigations showed elevated amylase, ultrasound abdomen revealed acute pancreatitis.She had undergone a laparotomy elsewhere.Examination showed generalised pigmented rash, alopecia, periorbital puffiness, hard palatal ulcer, surgical scar on the abdomen.Investigations showed anemia, normal platelet count, elevated ESR, normal renal functions, nephrotic range proteinuria, elevated serum amylase.Ultrasound and CT abdomen revealed a pancreatic pseudocyst.A clinical possibility of SLE with acute pancreatitis and lupus nephritis was considered.Further investigations were suggestive of lupus(table).Workup for APLA revealed positive lupus anticoagulant.Her skin biopsy was consistent with lupus and renal biopsy revealed class 4 lupus nephritis.She was initiated on oral prednisolone and was given pulses of intravenous cyclophosphamide.There has been no recurrence of pancreatitis over 12 years follow-up. Conclusions: Pancreatitis can at times, be the presentation of childhood lupus and requires prompt and aggressive management. Funding Source(s): None